Rectal application of a highly osmolar personal lubricant in a macaque model induces acute cytotoxicity but does not increase risk of SHIV infection. - Sundaram A Vishwanathan; Monica R Morris; Richard J Wolitski; Wei Luo; Charles E Rose; Dianna M Blau; Theodros Tsegaye; Sherif R Zaki; David A Garber; Leecresia T Jenkins; Tara C Henning; Dorothy L Patton; et al. (PLoS ONE)
Background Personal lubricant use is common during anal intercourse. Some water-based products with high osmolality and low pH can damage genital and rectal tissues, and the polymer polyquaternium 15 (PQ15) can enhance HIV replication in vitro. This has raised concerns that lubricants with such properties may increase STD/HIV infection risk, although in vivo evidence is scarce. We use a macaque model to evaluate rectal cytotoxicity and SHIV infection risk after use of a highly osmolar (>8,000 mOsm/kg) water-based lubricant with pH of 4.4, and containing PQ15. Methods Cytotoxicity was documented by measuring inflammatory cytokines and epithelial tissue sloughing during six weeks of repeated, non-traumatic lubricant or control buffer applications to rectum and anus. We measured susceptibility to SHIVSF162P3 infection by comparing virus doses needed for rectal infection in twenty-one macaques treated with lubricant or control buffer 30 minutes prior to virus exposure. Results Lubricant increased pro-inflammatory cytokines and tissue sloughing while control buffer (phosphate buffered saline; PBS) did not. However, the estimated AID50 (50% animal infectious dose) was not different in lubricant- and control buffer-treated macaques (p = 0.4467; logistic regression models). Conclusions Although the test lubricant caused acute cytotoxicity in rectal tissues, it did not increase susceptibility to infection in this macaque model. Thus neither the lubricant-induced type/extent of inflammation nor the presence of PQ15 affected infection risk. This study constitutes a first step in the in vivo evaluation of lubricants with regards to HIV transmission.